Cellular autophagy, the compelling roles in hearing function and dysfunction - Wan, Huanzhi; Zhang, Yuanyuan; Hua, Qingquan (Frontiers in Cellular Neuroscience, 2022)
Sensorineural hearing loss (SNHL) is currently a major health issue. As one of the most common neurodegenerative diseases, SNHL is associated with the degradation of hair cells (HCs), spiral ganglion neurons (SGNs), the stria vascularis, supporting cells and central auditory system cells. Autophagy is a highly integrated cellular system that eliminates impaired components and replenishes energy to benefit cellular homeostasis. Etiological links between autophagy alterations and neurodegenerative diseases, such as SNHL, have been established. The hearing pathway is complex and depends on the comprehensive functions of many types of tissues and cells in auditory system. In this review, we discuss the roles of autophagy in promoting and inhibiting hearing, paying particular attention to specific cells in the auditory system, as discerned through research. Hence, our review provides enlightening ideas for the role of autophagy in hearing development and impairment.